ARTICULATING MARGINAL VOICES IN MO YAN’S THE GARLIC BALLADS - Suprajitno, Setefanus (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This paper analyses Mo Yan’s The Garlic Ballads. It examines how this novel gives voice to marginalized rural communities in contemporary China. Set against the backdrop of political repression and economic exploitation, the novel portrays the lived experiences of garlic farmers whose struggles are often excluded from dominant narratives. This study addresses the problem of how marginal voices, those of subaltern groups such as impoverished farmers, women, and the disabled, are articulated, suppressed, and reclaimed in the narrative, revealing the limits of representation in a hierarchical system that silences dissent. Employing subaltern studies theory, particularly Gayatri Spivak’s framework of the subaltern’s inability to “speak” within dominant discourses, the analysis examines characters like the blind minstrel Zhang Kou, whose ballads critique authority, and Jinju, whose resistance to patriarchal marriage norms underscores gendered oppression. The findings show that while marginal voices disrupt official narratives through acts of protest and folklore, they are often violently muted by state mechanisms, as seen in arrests and suicides, highlighting the novel’s critique of power imbalances. This paper concludes that Mo Yan’s work demonstrates how marginal voices, though systematically stifled by power, find crucial, albeit tragic, articulation through collective resistance, which challenge the structures that seek to render them mute.